Experimental study on thermo-hydraulic performance of a solar air heater with rectangular perforated duct inserts. (October 2021) - Arunkumar, H.S.; Kumar, Shiva; Vasudeva Karanth, K.
Graphical abstract: Highlights: Experimental investigation of a double pass single flow Solar Air Heater (SAH) with perforated absorber duct inserts. Effect of duct height, hole diameter and number of holes are investigated. Duct height ratio of 0.66, two row hole arrangement with hole diameter ratio of 0.096 shows the highest cross flow effect. A maximum thermal efficiency of 84.8% and thermo-hydraulic efficiency of 81.06% are achieved. Abstract: This paper examines the results of experiments conducted on a glazed solar air heater duct which is modified with an additional rectangular duct insert having perforation on its top surface. This modified rectangular duct of varying height is designed to split the incoming air into the absorber. This is presumed to create a pressure difference above and below the perforated surface that will enhance the convective heat transfer due to the cross-flow effect. It is observed from the experiments that the drop in pressure along the absorber passage decreases with an increase in the height, increase in hole diameter, and the number of rows of the hole. It is established from the experiments that thermal efficiency is found to be maximum for the height ratio (h/H) of 0.66 when compared to height ratios of 0.50 and 0.83, perforated duct inserts. Further, by varying the hole diameter ratio and the number of rows, it is noted that two rows of holes with hole diameter ratio of 0.096 configuration gives the maximum thermal efficiency of 84.8% and thermo-hydraulic efficiency of 81.06%.